THE EFFECT OF THE THINK-PAIR-SHARE STRATEGY ON STUDENTS’ SPEAKING PERFORMANCE (A QUASI-EXPERIMENTAL STUDY AT THE ELEVENTH GRADE OF SMAN 6 SELUMA IN ACADEMIC YEAR 2025/2026) - Ananda Harjono, Alystia; Rizal, Syamsul; Prandika Putra, Pebri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was prompted by students' low speaking performance, which was affected by restricted vocabulary, a deficiency in confidence, and insufficient opportunity to practice spoken English. This study sought to examine the effect of the Think-Pair-Share (TPS) strategy on the speaking performance of eleventh-grade students at SMAN 6 Seluma during the 2025/2026 academic year. The study utilized a quasi-experimental methodology featuring a nonequivalent pretest-posttest control group design. The sample comprised two groups: the experimental group with 28 students and the control group with 26 students. Data were gathered using speaking test conducted as pre-tests and post-tests. The findings indicated a notable enhancement in the experimental group, with the average score rising from 48.43 to 74.36. Simultaneously, the control group exhibited an increase from 47.08 to 49.38; however, the enhancement was less significant than that of the experimental group. Statistical analysis indicated a significance value of 0.000 (< 0.05), demonstrating that the Think-Pair-Share strategy significantly influenced students' speaking performance. Consequently, the Think-Pair-Share strategy shown efficacy in enhancing students' speaking performance.